The effects of meal transition diets on nursery pig growth performance in a commercial environment - C N Groesbeck; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2005)
A total of 2,016 pigs (initially 12.6 lb and 18 ± 2 d of age) were used in a 28-d growth assay to evaluate the current feed-budget allocations for SEW, Transition, and Phase 2 diets fed in meal form in a commercial environment. Pigs were allotted to one of six treatments, with a variety of feed budgets: 1) pelleted diets with 1 lb/pig of SEW diet (6.7% plasma) and 3 lb/pig of Transition diet (2.5% plasma); 2) pelleted diets with 0.5 lb/pig of SEW diet (6.7% plasma) and 1 lb/pig of Transition diet (2.5% plasma); 3) meal diet with 2 lb/pig Transition diet (2.5% plasma); 4) meal diet with 4 lb/pig of Transition diet (2.5% plasma); 5) meal diet with 2 lb Transition diet (4% plasma); and 6) meal diet with 4 lb Transition diet (4% plasma). After the allotted amount of feed was distributed to the pens as described in the budget, all treatments were fed 12 lb/pig of a Phase 2 meal diet, and then a Phase 3 meal diet for the duration of the trial. From day 0 to 10 and for the overall period, the pigs fed the pelleted SEW and Transition diets grew faster, and had better feed efficiency, lower removal rates (culls), and greater margin over feed cost than did the pigs fed the meal-based Transition diets. For pigs fed the pelleted SEW and Transition diets, pigs fed 1 and 3 lb, respectively, had better ADG and F/G for the period d 0 to 10 after weaning, better F/G for the period d 0 to 28, lower feed cost per lb of gain, and greater margin over feed than pigs fed 0.5 and 1 lb, respectively, of SEW and Transition diets. The current recommendations of providing weanling pigs 1 lb/pig SEW diet and 3 lb/pig Transition diet optimized growth and profitability in this production system.; Swine Day, 2005, Kansas State University, Manhattan, KS, 2005
Keywords: Swine day; 2005; Summary Publication of Report of Progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 964; Kansas Agricultural Experiment Station contribution; no. 06-63-S; Nursery pig; Pellets; Feed budget; Spray-dried animal plasma; Swine